ACCULTURATION VARIETY OF SUNDANESSE AND MODERN ARCHITECTURE AT SELASAR SUNARYO ART SPACE IN BANDUNG - Gabriella Serena ; Bachtiar Fauzy (Riset Arsitektur (RISA), 2019)
Abstract- The growth of globalization is a worldwide phenomenon that is unavoidable and its impact affects a lot of fields, including architecture. Non-local elements, like modernism, that penetrate Indonesia’s culture cause a competition against the local architecture including traditional values, which are reduced due to modernization. Combining modern and local architecture can be seen as an effort to conserve traditional values and answer to the era’s challenge at the same time through the application of modernization.The aim of this research is to understand the meaning of acculturation in architecture, discover which acculturation that occurs in Selasar Sunaryo Art Space architecture and discover what domination that exists in Selasar Sunaryo Art Space’s architecture. Study of synthesis of architecture in Selasar Sunaryo Art Space is done by doing firstly a survey to gain object data, undertake an interview with the architect and client to gain the architectural concept of the object, and re-model the object in 3D. Literature is also done to gain theories about acculturation in architecture, building anatomy theory to describe the study object, also Sundanese and modern architecture theories. Afterwards, the object is analyzed by the said theories and interpreted referring to literature.The result of this research shows that modern architecture dominates Selasar Sunaryo’s architecture, especially in it’s body, floor, structure, and ‘s shape. Synthesis of architecture can be seen from the landscape design and roof design. Overall, Selasar Sunaryo’s architecture is dominated by modern structure and arrangements, although there are several adaptations to the building’s climate context and application of Sundanese architecture concepts to its buildings.Hopefully this thesis would be beneficial to practitioners, academics, and people in general as a contribution to expand the knowledge of local and non-local architecture synthesis, also as a contribution of knowledge that is beneficial within designing process or of continuation of the research. Key Words: acculturation, architecture, modern, Sundanese